Accessibility and Affordability of Tertiary Education in Brazil, Colombia, Mexico and Peru within a Global Context - Murakami, Yuki; Blom, Andreas (World Bank, Washington, DC, 2012)
This paper examines the financing of tertiary education in Brazil, Colombia, Mexico and Peru, comparing the affordability and accessibility of tertiary education with that in high-income countries. To measure affordability, the authors estimate education costs, living costs, grants, and loans. Further, they compute the participation rate, attainment rate, and socio-economic equity index in education and the gender equity index as indicators of accessibility. This is the first study attempting to estimate affordability of tertiary education in Latin America within a global context. The analysis combines information from household surveys, expenditure surveys, and administrative and institutional databases. The findings show that families in Latin America have to pay 60 percent of per-capita income for tertiary education per student per year compared with 19 percent in high-income countries. Living costs are significant, at 29 percent of gross domestic product per capita in Latin America (19 percent in high-income countries). Student assistance through grants and loans plays a marginal role in improving affordability. Moreover, the paper confirms previous findings of low access to tertiary education in the region. One policy implication of the findings is that Latin American governments could take steps to make tertiary education more affordable through student assistance.